MANAM’MI: PEMBANGUNAN BERBASIS KEARIFAN LOKAL STUDI PADA MASYARAKAT MIANGAS KABUPATEN KEPULAUAN TALAUD - Sahadula, Frinsisika Jelinda; Therik, Wilson M.A. (Universitas Kristen Satya Wacana, 2017)
Manam'mi tradition contains a set of informal values ​​or norms, such as mutual trust, mutual understanding, equality in values ​​and behavior, mutual assistance, and mutual help that forms the structure of society and becomes a bond among the community members which is effective for coordination and cooperation in achieving the common goals. Manam'mi is one of coastal community local wisdom which contains marine resource management components. The Eha concept in a series of Manam'mi ritual embodies the natural resources sustainability as well as the marine ecosystem balance and provides opportunities for other living creatures to breed, so that the continuity of natural resources supplies on land and at sea are ensured. Sammi is the ecological intelligence of Miangas indigenous people in managing the marine resources by using environmentally friendly (eco-friendly) fishing gear. The focus of this study is to describe how the implementation of Manam'mi ritual in community life in Miangas Island is viewed from the sustainable development, social capital and culture capital perspective. This study used descriptive-qualitative approach. The approach was done by doing interview, observation, documentation study, and inductive model data analysis. Manam'mi tradition can be regarded as social capital of Miangas society because it involves belief, norms, and relationships/networks between the stakeholders. The study shows that Manam'mi contains three sustainable development approaches, namely environmental, economic, and socio-cultural approaches.